System $G|G^κ|1$ with Batch Service of Calls - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For the queuing system G|G κ|1 with batch service of calls, we determine the distributions of the following characteristics: the length of a busy period, the queue length in transient and stationary modes of the queuing system, the total idle time of the queuing system, the output stream of served calls, etc.